The concept of gender in researching women And entrepreneurship - Salmah Topimin; Irma Wani Othman; Haslinda Hasan; Siti Nor Bayaah Ahmad; Merlyn Rita Buncha (Academic Inspired Network, 2022)
Based on a review of the literature on the concepts of gender and women’s entrepreneurship, this paper highlights the importance of employing the gender approach in researching women in general and women entrepreneurs in particular. This paper makes the argument that to fully comprehend the phenomenon of women's entrepreneurship, research on the topic must consider the complexity of women's social environment. The complexity of women’s social environment is a result of a dynamic interactions between various individual and environmental factors that influence their decisions, actions, and behaviour. Within this context, women’s decision, action, and behaviour are learnt from their social environment. This social environment believes that the work of men and women can be segregated, thus causing women to act based on the gender roles that have been established by their social environment. This paper investigates the extent to which gender has a significant influence on women entrepreneurs. Therefore, if the social environment that controls women's lives is ignored, the reality of women entrepreneurs' entrepreneurial experiences cannot be represented. Furthermore, the common practice of conducting research that inadequately acknowledges the distinctions between women and men has contributed to the idea that women entrepreneurs are less successful than men. Therefore, this paper explores the bias that surrounds our understanding of women entrepreneurs and suggests how the bias can be reduced by applying the gender concept as a foundation for women’s entrepreneurship research.